2004
DOI: 10.1657/1523-0430(2004)036[0446:mcaatr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modern Chironomid Assemblages and Their Relationship to Physical and Chemical Variables in Southwest Yukon and Northern British Columbia Lakes

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Previous studies have documented chironomid distributions in lake sediments from northern North America, including treeline in central Canada (Walker & MacDonald, 1995), eastern Canada, including several sites from Devon Island and southern Baffin Island (Walker et al, 1997), Yukon and the Mackenzie Delta region (Walker et al, 2003) and the southwest Yukon (Wilson & Gajewski, 2004). Data presented here extend the distribution northward to encompass the Highand Middle-Arctic of Canada.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies have documented chironomid distributions in lake sediments from northern North America, including treeline in central Canada (Walker & MacDonald, 1995), eastern Canada, including several sites from Devon Island and southern Baffin Island (Walker et al, 1997), Yukon and the Mackenzie Delta region (Walker et al, 2003) and the southwest Yukon (Wilson & Gajewski, 2004). Data presented here extend the distribution northward to encompass the Highand Middle-Arctic of Canada.…”
Section: Discussionsupporting
confidence: 55%
“…Corynocera ambigua was reported in many lakes from the Northwest Territories (Walker & MacDonald, 1995) and Yukon (Walker et al, 2003;Wilson & Gajewski, 2004). Walker et al (2003) considered this species a Beringian taxon, as it is not found in Quebec/Labrador, nor to the south of 60 o N in North America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern organism assemblages from southwestern Yukon, including pollen (Birks, 1977;Lacourse, 1998;Whitmore et al, 2005), diatom (Wilson and Gajewski, 2002), chironomid (Wilson and Gajewski, 2004), and ostracode (Bunbury and Gajewski, 2005) assemblages, have also been analyzed in relation to the environment. Several characteristics of the lake environment (e.g., water depth, organic matter content of the sediments, and water chemistry) affect the composition of the species assemblages found in these lakes.…”
Section: Modern Studies For Interpreting Paleoenvironmental Datamentioning
confidence: 99%
“…This study was motivated by discussions with researchers attempting to explain the spatial patterning of plant communities in and around the Kluane region of northwestern Canada, as well as our own work developing calibration equations for quantitative paleoclimate reconstructions (e.g., Wilson andGajewski, 2002, 2004;Bunbury and Gajewski, 2005). Although southwestern Yukon is an ideal location for studying mountainous environments, very few climate data are available.…”
Section: Introductionmentioning
confidence: 99%